Grundtvig og Det litterære Selskab 1805-1822 - Lundgreen-Nielsen, Flemming (Grundtvig-studier, 1982)
Grundtvig and Literary Society 1805-1822 By Flemming Lundgreen-Nielsen In the period July 3rd 1808 to January 1810 Grundtvig was a member of a largely unknown reading society comprising students and lower civil servants. Through the club he received advice and the chance to keep up-to-date with a number of literary magazines, to which he himself also contributed articles.The discovery of the reading society and Grundtvig’s membership was made in the hand-written collections at the Royal Library in Copenhagen, where the society’s papers are kept in three files (New Royal Collection 1218 f,g and h 4°). In this article Dr. Flemming Lundgreen-Nielsen considers the discovery and importance of Grundtvig’s membership. In this connection he contributes further information as to how in his early years Grundtvig found opportunities to satisfy his colossal need for reading.